Pengaruh Profitabilitas, Likuiditas, Leverage, Opinion Shopping dan Ukuran Kap terhadap Opini Audit Going Concern: Studi Empiris Pada Sektor Property dan Real Estate yang terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Dewi Widhyastuti; Desy Mariani (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
This study aims to analyze the influence of Profitability, Liquidity, Leverage, Opinion Shopping, and Public Accounting Firm (KAP) Size on Going Concern Audit Opinion in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The audit opinion going concern is an important issue because it reflects the company's ability to maintain its business continuity in the midst of economic uncertainty and increasingly complex market dynamics. The research population includes all companies in the property and real estate sectors on the IDX, with sample selection using purposive sampling techniques that resulted in 60 companies as the object of the study. The collected data was analyzed using the logistic regression method to test the influence of each independent variable on the audit opinion going concern. The results of the study show that profitability has a negative and significant effect on the audit opinion of going concern, which means that the higher the level of profitability of the company, the less likely the auditor to give an audit opinion of going concern. Furthermore, Opinion Shopping has been proven to have a positive and significant effect on going concern audit opinions, so that the practice of seeking alternative auditor opinions has the potential to increase the risk of issuing going concern opinions. Meanwhile, the variables Liquidity, Leverage, and KAP Size did not show a significant influence on the audit opinion going concern. These findings confirm that certain financial performance factors as well as management behavior in seeking auditor opinions have an important role in determining audit opinion going concern, while other factors such as the size of the KAP are not necessarily determinative.